Evaluation of the Interaction Model of Client Health Behavior‐based multifaceted intervention on patient activation and osteoarthritis symptoms. Issue 2 (19th November 2019) - Ahn, Yang Heui; Ham, Ok Kyung
Abstract: Purpose: This study evaluated a multifaceted intervention for osteoarthritis symptoms. Methods: A cluster randomized controlled trial was conducted with a convenience sample of 90 patients aged between 45 and 82 years, who were recruited from three Community Health Posts (CHPs). The CHPs were randomized into two experimental groups (E1 and E2) and one control group (C). The intervention included health education and counseling combined with exercise classes based on the Interaction Model of Client Health Behavior. Trained community health nurse practitioners led the intervention. Stretching exercise (E1) and walking (E2) combined with muscle strengthening exercise were provided. The instruments included the Patient Activation Measure (PAM), Korean version of the Western Ontario and McMaster Universities Osteoarthritis Index (K‐WOMAC), Stanford Health Assessment Questionnaire Disability Scale (HAQDS), and Center for Epidemiologic Studies Depression Scale (CES‐D). The HAQDS was measured using an ordinal scale, and Likert scales were used for the other instruments. Chi‐square test and analysis of covariance were used; P values <.05 were considered significant. The study was conducted in 2014. Results: The groups were similar at the baseline ( P > .05) except for joint pain and patient activation ( P < .05). At post‐test, the changes in the mean scores were significant for joint pain and stiffness, and physical functioning. E2 with walking exercise showed better improvements in joint pain and physical functioning than the other groups ( P < .01). Conclusions: Eight sessions of multifaceted intervention improved the osteoarthritis symptoms. Follow‐up studies will be needed to determine the intermediate and long‐term effects of the multifaceted intervention.